2010
DOI: 10.1002/app.32172
|View full text |Cite
|
Sign up to set email alerts
|

Pectin grafted poly(N‐vinylpyrrolidone): Optimization and in vitro controllable theophylline drug release

Abstract: The present article describes preparation, optimization, and characterization of pectin grafted polyvinylpyrrolidone hydrogels followed by controllable theophylline drug release. The gels were prepared in the presence of N,N 0 -methylenebisacrylamide (MBAA) crosslinker and ceric ammonium nitrate (CAN) initiator under N 2 atmosphere. Optimum conditions, in terms of percent of grafting (%G), were determined as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 32 publications
(25 reference statements)
3
23
0
Order By: Relevance
“…Such results clearly demonstrated that pectin is strongly bonded to polycaprolactone in large amounts of crystalline PGP that decomposed at 400°C, and consequently, very small amounts of amorphous PGP exist. In previous works, amorphous or low‐crystalline pectin grafted polymers showed split of decomposition peaks of pectin and other polymers . Such results came in accordance with high percentage of crystallinity of PGP determined in DSC results and also with ATR‐FTIR results.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Such results clearly demonstrated that pectin is strongly bonded to polycaprolactone in large amounts of crystalline PGP that decomposed at 400°C, and consequently, very small amounts of amorphous PGP exist. In previous works, amorphous or low‐crystalline pectin grafted polymers showed split of decomposition peaks of pectin and other polymers . Such results came in accordance with high percentage of crystallinity of PGP determined in DSC results and also with ATR‐FTIR results.…”
Section: Resultssupporting
confidence: 87%
“…In previous works, amorphous or low-crystalline pectin grafted polymers showed split of decomposition peaks of pectin and other polymers. [50][51][52] Such results came in accordance with high percentage of crystallinity of PGP determined in DSC results and also with ATR-FTIR results.…”
Section: High Crystalline and High Thermally Stable Pgpsupporting
confidence: 88%
“…The results were analyzed using Xpert high score (version 1.0 b, Philips analytical B.V.). The % crystallinity of the samples was determined as per the equation given below19: …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the area under the curve was used to observe the ratio of aliginic acid to poly(methacrylamide) fractions in the formed hydrogel as depicted in Fig. . It can be seen that aliginic acid shows a sharp decomposition temperature peak at 242 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%